2006
DOI: 10.1152/physiolgenomics.00320.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling the gills of amoebic gill disease (AGD)-affected Atlantic salmon (Salmo salarL.): a role for tumor suppressor p53 in AGD pathogenesis?

Abstract: Neoparamoeba spp. are amphizoic amoebae with the capacity to colonize the gills of some marine fish, causing AGD. Here, the gill tissue transcriptome response of Atlantic salmon ( Salmo salar L.) to AGD is described. Tanks housing Atlantic salmon were inoculated with Neoparamoeba spp. and fish sampled at time points up to 8 days postinoculation (pi.). Gill tissues were taken from AGD-affected fish, and a DNA microarray was used to compare global gene expression against tissues from AGD-unaffected fish. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 87 publications
4
69
1
Order By: Relevance
“…Ourth et al (2007) have suggested that MBL could be used as a genetic marker for disease resistance in the different strains of cultured catfish, as those more resistant to Edwardsiella ictaluri had nearly three fold higher levels of serum MBL. In other infection studies the transcriptomic responses of MBL were dependent on the pathogen involved, as demonstrated by the 4.2-fold down-regulation of the MBL gene in the gills of AGD-affected Atlantic salmon (Morrison et al, 2006), and the 2-fold up-regulation in juvenile Atlantic salmon infected with saprolegniasis, a fungal infection (Roberge et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Ourth et al (2007) have suggested that MBL could be used as a genetic marker for disease resistance in the different strains of cultured catfish, as those more resistant to Edwardsiella ictaluri had nearly three fold higher levels of serum MBL. In other infection studies the transcriptomic responses of MBL were dependent on the pathogen involved, as demonstrated by the 4.2-fold down-regulation of the MBL gene in the gills of AGD-affected Atlantic salmon (Morrison et al, 2006), and the 2-fold up-regulation in juvenile Atlantic salmon infected with saprolegniasis, a fungal infection (Roberge et al, 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Other immune parameters such as the phagocytic activity of macrophages and/or respiratory burst of leukocytes were also decreased in different hosts infected with other parasites (Mustafa et al, 2000;Fast et al, 2002;Scharsack et al, 2004;Karagouni et al, 2005). At the transcriptional level, the parasite-mediated amoebic gill disease (AGD) in Atlantic salmon produced a marked up-regulation of gene expression in early stages (4-8 days) of infection (Morrison et al, 2006), whereas at medium (19 days) (Wynne et al, 2008a) and long term exposure (36 days) (Young et al, 2008), a strong overall gene suppression was evident in the immune response, transport, translation and catalytic activity functional categories. This late suppression is in accordance with that observed in the present model of long term exposure to the myxosporean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferon type I and type II responses in an Atlantic salmon (Salmo salar) SHK-1 cell line by the salmon TRAITS/SGP microarray. Physiol Genomics 32: [33][34][35][36][37][38][39][40][41][42][43][44] 2007. First published September 5, 2007; doi:10.1152/physiolgenomics.00064.2007 RNA was hybridized to an Atlantic salmon cDNA microarray (salmon 17K feature TRAITS/SGP array) in order to assess differential gene expression in response to IFN exposure.…”
mentioning
confidence: 99%
“…As shown in Fig. 1B, CagAgr2 belongs to the fish Agr2 family including zebrafish ZAgr2, Atlantic salmon SAgr2 (Morrison et al, 2006) and pufferfish TAgr2. Moreover, this fish branch is grouped together with a branch including human HAGR2, mouse MAgr2 and chicken CAgr2 with a high bootstrap value (94% support), suggesting a closer relationship among these Agr2 genes.…”
Section: Molecular Characterization Of Cagagr2mentioning
confidence: 99%